ANALISIS FAKTOR YG BERHUBUNGAN DENGAN PENYALAHGUNAAN NAPZA DI BANGKINANG KOTA TAHUN 2018 - Ade Dita Puteri; Ria Irena (Universitas Pahlawan, 2018)
The United Nations Office of Drugs and Crime (UNODC) places Indonesia in the 10 highest ranking countries for the distribution of ecstasy and cannabis drugs. The phenomenon of drugs itself is like an iceberg (ice berg) which means it appears on the surface smaller than the unseen. The purpose of this study was to determine the relationship of personality, family, and environment with drug abuse in Kampar District 2018. The design used in this study was retrospective descriptive with a case control approach. The sample in this study were 82 people for the case group and 82 control groups. The sampling technique is simple random sampling, the data collection tool that will be used in this study is in the form of a questionnaire. The analysis used is univariate and bivariate analysis. The results showed that based on personal factors p = 0.01 and OR 2.44 (C195%: 1.27-4.67) with the degree of significance (Î± = 0.05). This means there is a significant relationship between personality and drug use in Kampar District. Based on family factors obtained p values of 0.02 and OR 2.11 (C1 95%: 1.13-3.96), this means that there is a significant relationship between the criteria of broken home families with the occurrence of drug abuse and based on environmental factors obtained p value